Mantle Potential Temperature Estimates of Basalt from the East Taiwan Ophiolite - Shellnutt, J. Gregory; Hsieh, Robert B.-J. (TAO : Terrestrial, atmospheric, and oceanic sciences, 2016)
The East Taiwan Ophiolite (ETO) is a fragment of the eastern-most South China Sea that was accreted to the Eurasian margin during the Pliocene and is a member of the Western Pacific and Cordilleran belt ophiolite group. Ophiolites from the Western Pacific and Cordilleran belt are typically subduction-related (i.e., supra-subduction or volcanic-arc) but the ETO is compositionally, isotopically and mineralogically similar to subduction-unrelated ophiolites. The primary melt compositions of ETO basaltic rocks were calculated and range from high-Mg basalt to picrite (i.e., MgO = 10 to 14 wt%). The mantle potential temperature (T_P) estimates are within the range of ambient mantle (1300 - 1400°C) and other mid-ocean ridge ophiolites (i.e., Macquarie Island and Masirah) indicating that it is consistent with a mid-ocean ridge setting. Mantle potential temperature estimates for rocks from a mantle-plume-type ophiolite (i.e., 1620 - 1630°C) are anomalously high whereas rocks from supra-subduction zone ophiolites show a wider range that extends from ambient (i.e., Troodos and Semail) T_P to very high (i.e., Betts Cove and Bay of Islands) T_P.